Sebab, Akibat dan Terapi Pelaku Homoseksual - Abdurraafi’ Maududi Dermawan (PSGA LP2M IAIN Pontianak, 2016)
Homosexual is an attraction feeling, sexually, to people of one’s own sex. Based on the internal factor, homosexual people – from teenager age – basically have feelings and tendency only to men not women. Meanwhile, from the external aspect, homosexual is done because of friends, lifestyle, or environment. Furthermore, the internal aspect of homosexual is due to genetic factor. Children who were born with genetic and hormonal disorders would grow up based on their sexual deviance. Besides, the external aspect of homosexual comes from outside. In addition, the external factors could be begun from parental education, neighborhood, physic or psychological abuse, social-media effects, and friendships. As a result, the homosexual doer would have unnecessary future, morally or socially. Moreover, the psychological and religious approach would be needed. The therapy is demanded in order to restore the awareness of homosexual doers about their true identity as human.